Personal risk and protective factors involved in aggressive behaviour. - Gómez-Leal, Raquel; Megías-Robles, Alberto; Gutiérrez-Cobo, María José; Cabello-González, Rosario; Fernández-Berrocal, Pablo (My University, 2020)
The study of aggression plays a prominent role in psychology and public health, because of the important adverse consequences of such behaviour for victims, aggressors, and society in general. The General Aggression Model (GAM) provides a general conceptual framework for understanding the aggressive as a result of three stages: 1) inputs: personal and situational factors; 2) present internal states: affect, cognition, and arousal; and 3) outcomes: decision processes with a (non) aggressive result. The main objective of this research was to study the personal protective and risk factors most strongly associated with aggressive behaviour acting at the first stage of the GAM model. A total of two hundred and eighty-two young adult participants took part in this study. Participants were assessed for aggression levels and a set of the most relevant variables that have been associated with aggressive behaviour in the previous literature. Stepwise multiple regression analysis revealed that levels of aggression were mainly associated (73.2% of the explained variance) with the following protective factors: the ability to manage emotions as a component of EI, and perspective taking and personal distress as components of empathy; and with the following risk factors: negative and positive urgency as a component of impulsivity, fantasy as a component of empathy, negative affect, and expressive suppression of emotions. These findings provide a better understanding of the mechanisms underlying aggressive behaviour and provide greater empirical value to the current theoretical models. In addition, this research can help to inform the design of more successful programs for the prevention, control, and treatment of aggressive behaviour. Limitations and future lines of research are discussed.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/9304
Keywords: Agresividad - Aspectos psicológicos; Inteligencia emocional; Aggression; Protective factors; Emotional intelligence; Empathy; Negative affect; Impulsivity